Phylogenetic analysis of influenza A(H1N1)pdm viruses isolated in Ukraine during the 2009–2010 pandemic season - Leibenko, L.V.; Polischuk, V.P.; Mironenko, A.P. (Вiopolymers and Cell, 2013)
Aim. To perform the phylogenetic analysis of segments, encoding hemagglutinin and neuraminidase of A(H1N1) pdm influenza viruses, isolated in Ukraine. Methods. In this study the real-time polymerase chain reaction (RT-PCR), sequencing and phylogenetic analysis methods were used. Results. Key mutations in amino acid sequences of proteins of Ukrainian pandemic influenza isolates were analyzed. High genetic similarity of Ukrainian and foreign pandemic isolates (99 %) was observed. Conclusions. The stability of Ukrainian isolates genes during 2009–2010 pandemic season was shown. Мета. Здійснити філогенетичний аналіз сегментів, кодуючих гемаглютинін та нейрамінідазу пандемічних вірусів грипу A(H1N1) pdm, виділених в Україні. Методи. Полімеразно-ланцюгова реакція у реальному часі (real-time RT-PCR), секвенування і філогенетичний аналіз. Результати. Проаналізовано ключові мутації в амінокислотних послідовностях поверхневих антигенів досліджуваних вірусів. Виявлено високу генетичну подібність (99 %) українських ізолятів до вірусів, виділених в інших країнах. Висновки. Показано стабільність генів українських ізолятів протягом пандемічного сезону 2009–2010 рр. Цель. Осуществить филогенетический анализ сегментов, кодирующих гемагглютинин и нейраминидазу пандемических вирусов гриппа A(H1N1)pdm, выделенных в Украине. Методы. Полимеразная цепная реакция в реальном времени (real-time RT-PCR), секвенирование и филогенетический анализ. Результаты. Проанализированы ключевые мутации в аминокислотных последовательностях поверхностных антигенов исследуемых вирусов. Выявлено высокое генетическое сходство (99 %) украинского изолятов и вирусов, выделенных в других странах. Выводы. Показана стабильность генов украинских изолятов во время пандемического сезона 2009–2010 гг.